Experiments in competitive product positioning: An equilibrium analysis - Ulf G. Marks; Sönke Albers (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1995)
Almost all of the results on competitive product positioning derived in respective literature so far are based fimdamentally on the hypothesis that Nash-equilibria are "accurate predictions" of final market configurations. If the positioning behavior of firms differs from this assumed Nash-behavior, the corresponding propositions can no longer be used for optimal product positioning. In order to test the Nash-reaction hypothesis we used a newly developed marketing Simulation game PRODSTRAT to observe decisions of 240 advanced marketing students on product position, price and marketing budget under market conditions varied experimentally. Our results show that pricing and budgeting decisions are very well described by Nash-equilibria in the case of fixed product positions, while decisions on product positioning are significantly more competitive. The experiments have led to less differentiated market configurations with the consequence of increasing pricing as well as budgeting competition and significantly reduced profits. The rather more aggressive product positioning observed here seems to stem from attempts to reduce profit differences relative to the market leader and from strategies to lower the risk of possible profit losses in case of competitors' attacks. Aggressive positioning behavior compared to corresponding Nash-behavior was particularly observed in duopolistic markets, in markets with unimodal ideal point distributions and under market conditions with a low quality effect on consumers' preferences. However, deviations from Nash-behavior can only partly be explained by market conditions and seem to depend substantially on the personality of the respective competitors.
Keywords: 650; Marketingmanagement; Planspiel; Spieltheorie; Theorie